Traumatic mesenteric pseudocyst - Micković, Saša; Bezmarević, Mihailo; Nikolić-Micković, Irena; Mitrović, Miroslav; Tufegdžić, Ivana; Mirković, Darko; Sekulović, Leposava; Trifunović, Bratislav (Vojnosanitetski pregled, 2014)
Introduction. Mesenteric pseudocysts have rarely been described in literature. They belong to a group of mesenteric cysts that are very rare intra-abdominal pathology regardless of the origin. The diagnosis is often difficult to make, because of the diversity of clinical symptoms. The definitive histopathological diagnosis determines the origin and further course of treatment. Case report. We reported a patient with post-traumatic mesenteric pseudocyst. It was localised on the mesenteric side, in the direct contact with the small intestine. We surgically removed the pseudocyst along with a part of the small intestine with success. The patient’s recovery was eventless, with no complications. Conclusion. Only by complete cyst removal, the definitive, accurate histopathological diagnosis and classification can be made.
Keywords: mesentery; cystis; diagnosis; differential; digestive system surgical procedures